The content of the Konstantinos G. Karamanlis Archive: its european dimension - Minotos, Marietta (Revista General de Información y Documentación, 2009)
Every researcher as well as anyone interested in learning about the European course of Greece, turning to the sources preserved in Greek archives, shall be limited to the pertinent archival material kept in private collections since the corresponding materials are not yet accessible in public archives. Among the private archival collections, the archive of Konstantinos Karamanlis occupies a prime position, given that during his personal governance Greece’sAssociation (1961) with andAccession to the EEC (1979) took place. What were the circumstances that led to the taking of this specific decision that has been since then the main axis of Greek foreign policy?Were there concerns and dilemmas? How did the politicians of the country deal with these issues? What role was played by the representatives that handled these issues? How decisive was the international state of affairs? Which countries and political leaders rallied behind the Greek petitions? What were the European beliefs of Konstantinos Karamanlis? The scholar investigating the events of that specific period is called upon to give responses to these very questions.